Hematoma espontáneo de faringolaringe y anticoagulación. Descripción de un caso - CASASOLA GIRÓN, Marleny (2016)
Introduction and Objective: Spontaneous pharyngeal-laryngeal hematoma shows the importance of a complete ENT examination in the face of symptoms of banal appearance and a correct history that, in the case reported, unveiled the therapeutic use of anticoagulants. Case description: A 55 year old woman comes to emergency because of unexplained dysphagia. The inspection shows the presence of a hematoma in the pharyngeal-laryngeal region that, after the anticoagulant therapy was reversed, evolved favorably with conservative treatment. Discussion: In this case, apart from medical management performed by the hematology department, we focus our therapeutic approach in the protection of the airway and the prevention of a possible massive bleeding. Determining which patients require endotracheal intubation or tracheostomy and hemostatic surgery is the key to treatment. Conclusions: The anticoagulant therapy involves several complications that ENT specialists must consider in the face of clinical symptoms of dysphagia, dysphonia, dyspnea or signs of bleeding and they must know the possibilities of performance depending on the severity of each case.